2017
DOI: 10.1007/s00127-017-1341-9
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce discrimination and stigma: the state of the art

Abstract: BackgroundThere is a rich literature on the nature of mental health-related stigma and the processes by which it severely affects the life chances of people with mental health problems. However, applying this knowledge to deliver and evaluate interventions to reduce discrimination and stigma in a lasting way is a complex and long-term challenge.MethodsWe conducted a narrative synthesis of systematic reviews published since 2012, and supplemented this with papers published subsequently as examples of more recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
274
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 305 publications
(299 citation statements)
references
References 72 publications
19
274
1
5
Order By: Relevance
“…Third, the media campaign used indirect contact with the person with AD as the strategy for change. While contact was found to be a better strategy than education or protest to reduce stigma, it should be noted that direct, face‐to‐face contact was found to be preferable to indirect, parasocial contact, such as the contact used through the media. Finally, the Israeli campaign presented a positive rather than negative framing which, as stated above, was found to be less effective than a negative frame hinting at death and deterioration…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, the media campaign used indirect contact with the person with AD as the strategy for change. While contact was found to be a better strategy than education or protest to reduce stigma, it should be noted that direct, face‐to‐face contact was found to be preferable to indirect, parasocial contact, such as the contact used through the media. Finally, the Israeli campaign presented a positive rather than negative framing which, as stated above, was found to be less effective than a negative frame hinting at death and deterioration…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while many studies have reported on the impact of media campaigns on stigma associated with mental illness, only 2 previous studies have been published on a comparable topic in the area of AD. Wise, in a posttest‐only study conducted among 1689 adults after a campaign aimed at educating the public about AD, found that 53% reported they did not know enough about the disease, and 81% supported the statement that persons with dementia can still take part in normal activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the core motivations for reducing discrimination against individuals with mental health problems is that discrimination constricts the range of social contexts in which they can fully participate (Gronholm, Henderson, Deb, & Thornicroft, 2017). Reducing such discrimination, it is hoped, would allow people with mental health problems to participate more fully and be more productive.…”
Section: Discussionmentioning
confidence: 99%